Measurement of J/psi photoproduction at large momentum transfer at HERA - Chekanov, S.; Derrick, M.; Magill, S.; Musgrave, B.; Nicholass, D.; Repond, J.; Yoshida, R.; Mattingly, M.C.K.; Antonioli, P.; Bari, G.; Bellagamba, L.; Boscherini, D.; et al. (Springer Verlag, 2010)
The proton-dissociative diffractive photoproduction of J/psi mesons has been studied in ep collisions with the ZEUS detector at HERA using an integrated luminosity of 112 pb(-1). The cross section is presented as a function of the photon-proton centre-of-mass energy and of the squared four-momentum transfer at the proton vertex. The results are compared to perturbative QCD calculations.